On the Limits between Metaphysics and Science - Laskienė, Skaistė (Problemos, 1996)
Metaphysics as philosophical discipline is an inquiry into the ultimate nature of existence (as in Aristotle) and knowledge (as in Kant). There are no such definite problems in metaphysics as in science. Its problems of the relation between the subject and the object are more general, fundamental than scientific ones and have no final solution. Latitude of metaphysical thought is more extent than scientific one because metaphysics is operating with theoretical, not empirical, methods of scientific thought, supplemented with insight.